Assessment of physical disability using Barthel index among elderly of rural areas of district Jhansi (U.P), India - Shubhanshu Gupta (Journal of Family Medicine and Primary Care, 2016)
Introduction: The health of the elderly will be an important issue defining the health status of a population. With the rise in aged population, there is a greater need to look into their physical disability aspects, which is otherwise neglected. The rationale behind the study is to assess the physical disability of the elderly living in rural area of Jhansi. The aims of the study were to study the prevalence of physical disability among the elderly of rural area, and to find out the factors and association affecting the physical disability. Methods: A community-based cross-sectional study was carried out in a Baragaon block of rural area of Jhansi, Uttar Pradesh, India, from July 2015 to October 2015. Multistage random sampling was performed. A total of 265 participants of age 60 years and above were selected. Physical disability was assessed using Barthel index. Appropriate data entry and statistical analysis were done in EpiInfo. Frequency tables were used to calculate the prevalence, and Chi-square test was used to find out the association. Results: The overall prevalence of physical disability was 23.4%. 70% belongs to the age group from 60 to 69 years. Physical disability was significantly higher among age group >80 years. Similarly, women were more affected with physical disability than men. Conclusions: High prevalence of physical disability is the major area of concern. More extensive postdischarge health facilities to be provided to elderly.